KORELASI PERKULIAHAN BERBASIS E-LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA - Muthmainnah Asmal (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the relationship between e-learning-based instruction and the learning motivation of Computer Science students at Universitas Pancasakti Makassar. A quantitative correlational research design was employed. The sample was selected using a non-probability sampling method, specifically saturated sampling, consisting of all 28 students from the 2024 cohort of the Computer Science program. Data were collected through two questionnaires: one measuring perceptions of e-learning-based instruction, and the other assessing students’ learning motivation. The data were analyzed using Pearson’s correlation coefficient, yielding an r-value of 0.550, which exceeds the critical r-value of 0.31. As a result, the null hypothesis was rejected in favor of the alternative hypothesis. These findings suggest a significant and positive correlation between e-learning-based instruction and students’ learning motivation.